Оцінювання антизапальних властивостей поверхні дентальних імплантатів залежно від типу обробки (частина ІІ) - Варжапетян, Сурен Діасович; Шишкін, Максим Андрійович; Строгонова, Тетяна Василівна; Кокарь, Оксана Олександрівна; Varzhapetian, S. D.; Shyshkin, M. A.; Strohonova, T. V.; Kokar, O. O. (Запорізький державний медико-фармацевтичний університет, 2024)
Мета роботи – дослідження антизапальних властивостей поверхні комерційних дентальних імплантатів зі сплавів цирконію і титану із різним методом обробки на прикладі перебігу першого етапу імплантації. Матеріали і методи. Досліджено структурні (мікроструктура поверхні, біосумісність, корозія поверхні, елементні структури поверхні) та клінічні (тяжкість періімплантиту та мукозиту, коефіцієнт стабільності імплантатів) характеристики дентальних імплантатів із цирконію з обробкою поверхні методом РЕО та імплантатів з титану поверхнею з обробкою DAE. Використано медіанний тест (χ2), тест Краскела–Волліса (H), однофакторний дисперсійний аналіз (F). Різницю параметрів вважали статистично значущою на рівні p ≤ 0,05. Результати. Поверхня РЕО мала монолітний шар поверхні з порами округлої форми у середньому 4,51 мкм2. Поверхня DAE мала багатогранну неправильну форму, майже 7–12 мкм2. На поверхні DAE виявлено вуглець (4,59 ваг%), кисень (6,16 ваг%) і сліди цинку. Суттєва відмінність елементного складу імплантатів РЕО полягала в наявності хлору (0,93 ваг%), силіцію (0,14 ваг%), алюмінію (0,23 ваг%), калію (0,47 ваг%) та магнію (0,07 ваг%). Результати порівняння контактного кута зразків DAE (29,2 ± 5,9°) та РЕО (21,5 ± 3,3°) не мали статистично значущої відмінності (р > 0,05). Після 7 діб експозиції в розчині SBF у цирконієвих імплантатів із поверхнею РЕО визначено збільшення кальцію (на 21,87 ваг%), фосфору (на 35,68 ваг%), натрію (на 72,89 ваг%) та хлору (на 76,21 ваг%). Більше не визначали алюміній, силіцій, цинк. Особливість зразка титанового імплантату з поверхнею DAE – лише фоновий рівень кальцію (0,06 ваг%) та відсутність фосфору; найбільш вагомо представлені кисень (16,71 ваг%), вуглець (12,37 ваг%), натрій (6,47 ваг%) і хлор (5,90 ваг%). Оцінювання адгезії клітин до поверхні зразків Zircon-Prior та B&B Dental ні на першу, ні на сьому добу інкубації не виявило статистично значущої відмінності. The aim. Study of the anti-inflammatory properties of the surface of commercial dental implants made of zirconium and titanium with different processing methods using the example of the course of the first stage of implantation. Materials and methods. The structural (microstructure of the surface, biocompatibility, surface corrosion, elemental surface structures) and clinical (severity of peri-implantitis and mucositis, coefficient of implant stability) characteristics of dental implants made of zirconium with surface treatment by the PEO method and implants made of titanium with DAE surface treatment were studied. Median test (χ2), Kruskal–Wallis test (H), univariate variance analysis (F) were used. The difference in parameters was considered statistically significant at the p ≤ 0.05 level. Results. The PEO surface had a monolithic surface layer with rounded pores averaging 4.51 μm2. The DAE surface had a polyhedral irregular shape, about 7–12 μm2. On the DAE surface: carbon – 4.59 wt%, oxygen – 6.16 wt% and traces of zinc were found. A significant difference in the elemental composition of PEO implants was the presence of chlorine (0.93 wt%), silicium (0.14 wt%), aluminum (0.23 wt%), potassium (0.47 wt%) and magnesium (0.07 wt%). The results of comparing the contact angle of the B&B Dental 29.2 ± 5.9° and Zircon-Prior 21.5 ± 3.3° samples had no statistically significant difference (р > 0.05). After 7 days of exposure in the SBF solution, zirconium implants with a PEO surface increased calcium by 21.87 wt%, phosphorus by 35.68 wt%, sodium by 72.89 wt%, and chlorine by 76.21 wt%. Aluminum, silicium, and zinc were no longer detected. The peculiarity of the titanium implant sample with the DAE surface was only the background level of calcium – 0.06 wt% and the complete absence of phosphorus; the most significant components were oxygen – 16.71 wt%, carbon – 12.37 wt%, sodium – 6.47 wt%, and chlorine – 5.90 wt%. Assessment of cell adhesion to the surface of Zircon-Prior and B&B Dental samples neither on the first nor on the seventh day of incubation did not demonstrate a statistically significant difference. Clinical signs of bone tissue resorption were identified around 30.8 % of implants with a PEO surface and 27.3 % of implants with a DAE surface (p = 0.8); inflammation of the mucous membrane – in the areas of installation of 34.6 % of PEO implants and 72.7 % of DAE (p = 0.009). 3.8 % of PEO implants and 9.1 % of DAE implants were lost (p = 0.44). The average ISQ were significantly different: 59.2 ± 4.1 DAE implants versus 64.4 ± 4.9 PEO implants, p = 0.003.
Evaluation of anti-inflammatory properties on the surface of dental implants depending on the type of processing (Part II)
Варжапетян С. Д. - ORCID ID: 0000-0001-5649-1126, 0000-0003-0464-6127; Шишкін М. А. - ORCID ID: 0000-0002-8979-8463; Строгонова Т. В. - ORCID ID: 0000-0001-5510-2176; Кокарь О. О. - ORCID ID: 0000-0001-7195-6999.
Keywords: титановий імплантат; обробка поверхні; періімплантит; метод обробки поверхні; коефіцієнт стабільності; запальне захворювання; комплексне лікування; dental implant; titanium; surface treatment; periimplantitis; method of surface treatment; stability factor; inflammatory disease; complex treatment